2013
DOI: 10.1021/jp3099413
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Astatine(III) Hydrolyzed Species: Experiments and Relativistic Calculations

Abstract: This work aims to resolve some controversies about astatine(III) hydroxide species present in oxidant aqueous solution. AtO(+) is the dominant species existing under oxidizing and acidic pH conditions. This is consistent with high-performance ion-exchange chromatography data showing the existence of one species holding one positive charge. A change in speciation occurs as the pH changes from 1 to 4, while remaining under oxidizing conditions. Dynamic experiments with ion-exchange resins evidence the existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 36 publications
2
77
0
Order By: Relevance
“…Two anionic species, A and B, were characterized by retention times of 5.2 min and 8.1 min, respectively, with a roughly 1:99 ratio between these two species (see Figure , top). The minor species, A, was identified as At − by comparison of retention times of samples prepared in the conditions in which this species assuredly predominates, both at neutral and acidic pH in reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Two anionic species, A and B, were characterized by retention times of 5.2 min and 8.1 min, respectively, with a roughly 1:99 ratio between these two species (see Figure , top). The minor species, A, was identified as At − by comparison of retention times of samples prepared in the conditions in which this species assuredly predominates, both at neutral and acidic pH in reducing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…11 Among the recent experimental highlights, it is worth quoting the determination of the ionization potential of the free atom, 12 or the determination of predominance domains in the Pourbaix diagram (E-pH) of At in aqueous solution. [13][14][15] One should also mention the theoretical prediction of a metallic behavior for condensed astatine, unlike the other halogens. 16 Furthermore, stable At cationic forms (At + and AtO + ) exist in aqueous solution and their coordination chemistry has been experimentally explored by reporting complexation constants with various inorganic ligands.…”
mentioning
confidence: 99%
“…Studies by other investigators on the redox chemistry of astatine have shown that under oxidizing and acidic pH conditions, AtO+ (At +3 hydroxide species) might be also present [1820]. Although it possibly could be a component of the At(1) peak, its presence becomes important only at pH much lower than those present in our experiments [21].…”
Section: Resultsmentioning
confidence: 52%